Australian square kilometre array pathfinder: I. system description. (5th March 2021) - Hotan, A. W.; Bunton, J. D.; Chippendale, A. P.; Whiting, M.; Tuthill, J.; Moss, V. A.; McConnell, D.; Amy, S. W.; Huynh, M. T.; Allison, J. R.; Anderson, C. S.; Bannister, K. W.; et al.
Abstract: In this paper, we describe the system design and capabilities of the Australian Square Kilometre Array Pathfinder (ASKAP) radio telescope at the conclusion of its construction project and commencement of science operations. ASKAP is one of the first radio telescopes to deploy phased array feed (PAF) technology on a large scale, giving it an instantaneous field of view that covers 31 deg^2 at 800 MHz . As a two-dimensional array of 36 × 12 m antennas, with baselines ranging from 22 m to 6 km, ASKAP also has excellent snapshot imaging capability and 10 arcsec resolution. This, combined with 288 MHz of instantaneous bandwidth and a unique third axis of rotation on each antenna, gives ASKAP the capability to create high dynamic range images of large sky areas very quickly. It is an excellent telescope for surveys between 700 and 1800 MHz and is expected to facilitate great advances in our understanding of galaxy formation, cosmology, and radio transients while opening new parameter space for discovery of the unknown.